Flexural behavior of reinforced concrete beams by using rice husk ash as partial replacement of fine aggregates in cement concrete - Chachar, Zameer Abbas; Ali, Imtiaz; Raza, Muhammad Saleem; Narwani, Tulsi Das; Raza, Ismail; Hussain, Mudasir (Penerbit Universiti Kebangsaan Malaysia, 2022)
Rice Husk has been utilized as a mineral admixture, cement replacement option, and filler in cement concrete as it provides several advantages such as improved strength values and environmental benefits related to the disposal of waste materials and to reduce the carbon dioxide emissions resulting from production of cement worldwide. In this study, flexural behavior of reinforced concrete beams using rice husk ash as a partial replacement of fine aggregates is investigated. For this purpose, four types of concrete mixtures were produced using rice husk ash as a partial replacement of fine aggregates at replacement levels of 0%, 10%, 15% and 20%. The produced reinforced rice husk ash concrete prism specimens were cured in water and tested to determine the ultimate load and ultimate deflection at 28 days of curing. The test results depicted that, the maximum ultimate load carried by reinforced rice husk ash concrete beam is 39.4 KN with 10% rice husk ash at 28 days and minimum ultimate load is 19.02 KN with 20% rice husk ash used as a partial substitute of fine aggregates at 28 days. The minimum ultimate deflection of 0.97mm occurred with 10% rice husk ash as a partial replacement of fine aggregate at 28 days of curing. Hence, this study concludes that 10% RHA can be utilized as a partial replacement of fine aggregates to provide strength in concrete and to reduce the environmental burden of rice husk waste. The results of this study will also provide a way forward to address the recent issues in construction sector, such as depletion of raw materials and increasing cost of construction.